2009
DOI: 10.2225/vol12-issue2-fulltext-12
|View full text |Cite
|
Sign up to set email alerts
|

Influence of metal ions and organic carbons on denitrification activity of the halotolerant bacterium, Paracoccus pantotrophus P16 a strain from shrimp pond

Abstract: Waste nitrogen containing compounds, of both organic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…The production of Fe(III)‐chelating and Fe(III)‐mobilizing siderophores in iron‐free grown cultures is also an indication for the high demand of iron by BoFeN1. A positive effect of Fe(III) addition on bacterial growth in general (Dehner et al ., ) and on denitrification (Baalsrud & Baalsrud, ; Pintathong et al ., ) has been demonstrated before. These authors observed increased nitrate utilization when the medium contained concentrations in the μ m range of Fe 3+ .…”
Section: Discussionmentioning
confidence: 78%
“…The production of Fe(III)‐chelating and Fe(III)‐mobilizing siderophores in iron‐free grown cultures is also an indication for the high demand of iron by BoFeN1. A positive effect of Fe(III) addition on bacterial growth in general (Dehner et al ., ) and on denitrification (Baalsrud & Baalsrud, ; Pintathong et al ., ) has been demonstrated before. These authors observed increased nitrate utilization when the medium contained concentrations in the μ m range of Fe 3+ .…”
Section: Discussionmentioning
confidence: 78%
“…The tubes were kept at room temperature for 60 min. Nitrite was assayed in supernatant (harvested from biomass by centrifugation at 4,830 g for 10 min) as described before [2,6].…”
Section: Nitrate Reduction Activity Of Native Cellsmentioning
confidence: 99%
“…Denitrification is typically occurring under anaerobic or anoxic conditions [6,[16][17][18]. In addition, microbially aerobic nitrate reduction has also been reported by soil bacteria such as Pseudomonas, Arthrobacter, Moraxella and Aeromonas [19][20][21].…”
Section: Screening Of Nitrate Reductase Positive-isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated in Figure 20, a high abundance of OTUs belonging to the genus Paracoccus was found in reactors RVC1, PL1, PL2 and PL3 (48, 10, 29 and 27% abundance respectively) and could be regarded as the main responsible for denitrification on the biofilms formed at the electrodes RVC1 and PL2. A few species of this genus are well known to perform denitrification [156][157][158] and they were also previously found in cathodic biofilms performing nitrate reduction [93,154]. A high abundance of OTUs belonging to the genus Paracoccus were also found at the PL1 and PL3 electrodes, although the role of denitrification on those reactors seem to be shared also by other groups of organisms such as Dechloromonas [159] (22 and 31% abundance respectively).…”
Section: Community Structure Assessmentmentioning
confidence: 62%